A NOVEL APPROACH TO SCLERAL FIXATION OF POSTERIOR CHAMBER INTRAOCULAR LENSES AND CAPSULAR TENSION RINGS AND SEGMENTS IN DEEP-SET EYES. Issue Volume 16:Issues 3(2022) (28th February 2020) - Miller, Charles G.; Minkus, Caroline; Lyon, Alice T.; Basti, Surendra; Leskov, Ilya
Abstract : The scleral fixation of posterior chamber intraocular lenses and capsular tension rings and segments present a unique surgical challenge in deep-set eyes. The Finesse FlexLoop (Alcon Laboratories) can be used as an alternative to 25-gauge forceps to more easily externalize Gore-Tex sutures in such cases. Abstract : Purpose: To demonstrate a novel approach to scleral fixation of posterior chamber intraocular lenses and capsular tension rings and segments in deep-set eyes using the Finesse FlexLoop (Alcon Laboratories). Methods: The technique described herein, based on previous approaches to scleral fixation of posterior chamber intraocular lenses, uniquely employs the FlexLoop to "lasso" Gore-Tex sutures that have already been threaded through the eyelets of a CZ70BD (Alcon Laboratories) IOL and externalize them. Results: All patients who underwent surgery with this technique experienced visual improvement. The only complication was of mild hyphema in the patient who had a capsular tension segment placed, which resolved with medical therapy. Conclusion: The advantages of this procedure include a smaller diameter instrument (FlexLoop) as compared to the 25-gauge forceps typically employed, an easier to perform surgical maneuver that alleviates the need for both precise placement and constant tension to be exerted by the surgeon to grasp the sutures, as well as an instrument that can function when bent up to 45° to help accommodate deep-set eyes requiring this procedure.